Proses Densifikasi Pelepah Sawit Menggunakan Crude Gliserol Sebagai Filler Menjadi Bahan Bakar Padat - Yudha, Ricky Satria; Helwani, Zuchra; Komalasari, Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Empty fruit bunches only used as a source of raw materials for animal feed, compost and organic fertilizer in the plantation. Palm empty fruit bunches has a calorific value of 18.795 kJ/kg. The calorific value can be increased by torefaction. Torefaction is one composing method with temperature 200 - 300°C to increase the density of the biomass so that it will increase the calorific value of the biomass. The purpose of this research is to produce solid fuel products from palm empty fruit bunches uses torefaction process, to determine the characteristics of the product and determine the effect of glycerol filler composition and pressure in the process of densification in density, calorific value and proximate. The variables for this research were glycerol filler composition (10, 20 and 30%) and pressure (50, 70 and 80 bar). The particle size used were less than 20 mesh. The highest density of the product was 0.6893 gr/cm3 which obtained at 10% composition and 50 bar. The lowest ash content of the product was 8.91% which obtained at 30% composition and 80 bar. The lowest moisture of the product was 0.91% which obtained at 10% composition and 80 bar. On the other hand, it produced highest fixed carbon and calorific value for 45.47% and 24011.77 kJ/kg, respectively.Keywords: torefaction, density, calorific value, filler, palm empty.